Bio-based carbon material modified ternary precursor as well as preparation method and application thereof
Through the two-step co-precipitation method and biomass carbon material coating technology, a ternary precursor with high spherical and stable shape was prepared, solving the shortcomings of nickel-rich NCM materials in terms of cycle stability and rate performance, and achieving efficient electrochemical performance improvement and environmentally friendly production.
Patent Information
- Application Number
- CN202411825873.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-12-12
AI Technical Summary
Nickel-rich NCM materials have shortcomings in cyclic stability and rate performance, mainly due to the random orientation of its spherical micron-scale secondary particles and the microstrain and cracks caused by the expansion/contraction of high anisotropic lattice.
A high spherical ternary precursor was prepared by a two-step co-precipitation method, and doped elements were added during the co-precipitation process to stabilize the crystal structure and improve the layer spacing of metal ions. The precursor surface is then coated with biomass carbon material to improve cycle stability and achieve the goal of green environmental protection.
The high spherical shape and uniformity of the ternary precursor are achieved, the crystal structure is stabilized, the transmission path of lithium ions is improved, the rate performance and cycle stability of the material are improved, and the production cost is reduced.
Smart Images

Figure CN119503911A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials and relates to a ternary precursor modified by a bio-based carbon material and a preparation method and application thereof. Background Art
[0002] Advanced cathode materials with high specific capacity are urgent materials to meet the growing demand for high energy density lithium-ion batteries. Among the many cathode candidate materials, Ni-rich (NCM) layered oxides can provide a high capacity of more than 200 mAh / g with an average discharge potential of 3.8 V (vs Li+ / Li). However, nickel-rich oxide cathode materials must overcome the problems of poor cycle stability and poor rate performance in practical applications. These defects are largely attributed to their spherical micron-sized secondary particles that are densely aggregated by many randomly oriented primary particles. On the one hand, along with this structure, the surface of the secondary particles is terminated by random crystal planes. Due to Li + In the layer structure of NCM materials, Li+ can only diffuse along the two-dimensional {010} plane, and the randomly exposed crystal planes may seriously hinder the exchange of Li+ at the electrode / electrolyte interface. + Ions need to cross grain boundaries, especially to migrate between grains with inconsistent crystal faces. Therefore, randomly oriented primary nanoparticles form a long Li + On the other hand, with the Li + The repeated intercalation and deintercalation and continuous phase transitions lead to anisotropic changes in the lattice parameters, which are severely exacerbated with increasing Ni content. Therefore, in nickel-rich oxide cathode materials, the massive anisotropic lattice expansion / contraction due to the non-synchronous volume can lead to severe microstrain at the boundaries of randomly oriented primary particles. As a result, cracks may develop and propagate along the grain boundaries until cracks occur in secondary particles or even primary particles peel off, which is one of the main reasons for the rapid decay of nickel-rich NCM materials in long-term cycles.
[0003] Existing technology improvements usually use doping, coating and other means to improve the electrochemical performance of positive electrode materials. Surface coating is mainly used to inhibit side reactions between the cathode and the electrolyte, while lattice ion doping is usually used to limit phase changes during charging and discharging and stabilize the crystal structure.
[0004] CN118610403A discloses a zirconium-fluorine co-doped NCM type high-nickel ternary positive electrode material, in which the zirconium element replaces the transition metal site and forms zirconium lithium oxide on the surface, and the fluorine element replaces the oxygen site. The stability of the material's crystal structure is enhanced, and the lithium ion diffusion and surface reaction kinetics are improved, thereby improving both the rate performance of the battery material and the cycle stability of the material.
[0005] CN118676350A discloses a modified positive electrode material, which suppresses the cracking of particles of the modified positive electrode material during the cycle process by co-doping with K and Si, enhances the stability of the structure of the modified positive electrode material, and improves the rate performance and cycle performance of the modified positive electrode material.
[0006] CN118630174A obtains a ternary positive electrode material by mixing a pre-sintered ternary positive electrode material matrix with a coating material containing La and performing secondary sintering to form a coating layer on the surface of the ternary positive electrode material matrix, and doping the rare earth element in the coating material into the ternary positive electrode material matrix. The ternary positive electrode material of the present application has high structural stability, conductivity, capacity and cycle stability.
[0007] However, the traditional surface coating and lattice ion doping modification technology cannot effectively solve the problem of layered particles in nickel-rich NCM materials. + The high anisotropy of diffusion and lattice expansion / contraction, morphology modulation will be an effective way to improve their rate performance and cycling stability. However, the structure and morphology controlled synthesis of NCM materials with superior rate and cycling performance remains a great challenge. Summary of the invention
[0008] The purpose of the present invention is to provide a ternary precursor modified by a bio-based carbon material, and a preparation method and application thereof. The present invention prepares a precursor with high sphericity by adjusting the conditions of the co-precipitation reaction through a two-step co-precipitation method. During the co-precipitation process, adding a suitable doping element can stabilize the crystal structure and improve the interlayer spacing of the metal ions. Then, the biomass carbon material is coated on the surface of the precursor to improve the cyclic stability of the precursor while achieving the purpose of green environmental protection and reducing costs.
[0009] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides a method for preparing a ternary precursor modified by a bio-based carbon material, the preparation method comprising the following steps:
[0011] (1) injecting a first nickel-cobalt-manganese mixed salt solution, a first complexing agent, a first precipitant, and a first doping metal source solution into a first base solution in parallel to perform a first coprecipitation reaction to obtain a core solution;
[0012] (2) adjusting the solid content of the core solution and the concentration of the first complexing agent to obtain a second base solution, and injecting a second nickel-cobalt-manganese mixed salt solution, a second complexing agent, a second precipitant, and a second doping metal source solution into the second base solution in parallel to perform a second coprecipitation reaction to obtain a doped ternary precursor;
[0013] (3) Carbonizing the bio-based carbon source to obtain a bio-based carbon-coated material, mixing the bio-based carbon-coated material with a doped ternary precursor, and sintering the mixture to obtain the ternary precursor modified by the bio-based carbon material.
[0014] The types of the first nickel-cobalt-manganese mixed salt solution and the second nickel-cobalt-manganese mixed salt solution, the types of the first complexing agent and the second complexing agent, the types of the first precipitating agent and the second precipitating agent, and the types of the first precipitating agent and the second precipitating agent of the present invention are respectively the same, and the "first" and "second" here are only to distinguish the adding steps.
[0015] The present invention improves the uniformity and consistency of precursor growth and the sphericity of the precursor through two-step co-precipitation. A doping metal source is added during the co-precipitation process. The doping element can improve the safety of the electrode material during the electrochemical reaction and the interlayer spacing of the metal ions. The obtained doped ternary precursor is then mixed with a biomass carbon source and sintered for coating. As a new type of material in the low-carbon and environmentally friendly economy, biomass material has a wide range of material sources, is green and environmentally friendly, and can be mass-produced. At the same time, it reduces dependence on traditional fossil fuel energy, injecting momentum into promoting China's green and low-carbon energy transformation.
[0016] Preferably, in step (1), the molar ratio of the total molar amount of the doping metal element in the first doping metal source solution to the total molar amount of the nickel, cobalt and manganese elements in the first nickel, cobalt and manganese mixed salt solution is (0.05-5):100, for example: 0.05:100, 0.1:100, 1:100, 2:100 or 5:100, etc., not limited to the listed values, other unlisted values within the numerical range are also applicable, preferably (0.5-1.5):100.
[0017] Preferably, the total mass concentration of nickel ions, cobalt ions and manganese ions in the first nickel-cobalt-manganese mixed salt solution in step (1) is 20 g / L to 120 g / L, for example: 20 g / L, 50 g / L, 80 g / L, 100 g / L or 120 g / L, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0018] Preferably, in step (1), the molar ratio of nickel ions, cobalt ions and manganese ions in the first nickel-cobalt-manganese mixed salt solution is (60-95):(1-20):(1-20), for example: 60:20:20, 65:18:17, 70:15:15, 80:10:10 or 95:2:3, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0019] Preferably, in step (1), the first complexing agent comprises aqueous ammonia.
[0020] Preferably, the mass concentration of the first complexing agent in step (1) is 5% to 10%, for example, 5%, 6%, 8%, 9% or 10%, etc., not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0021] Preferably, in step (1), the first precipitant comprises sodium hydroxide solution.
[0022] Preferably, the mass concentration of the first precipitant in step (1) is 20% to 40%, for example, 20%, 25%, 30%, 35% or 40%, etc., not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0023] Preferably, the doping metal source in the first doping metal source solution in step (1) includes any one of an aluminum source, a titanium source, a niobium source, a zirconium source, a tungsten source, a vanadium source, a strontium source, a gallium source, a cerium source, a yttrium source, a lanthanum source or an antimony source, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of a lanthanum source and an antimony source, a combination of an antimony source and a strontium source, or a combination of an antimony source and a gallium source, etc., preferably an antimony source.
[0024] Preferably, the antimony source includes any one of antimony trichloride, sodium antimonate, potassium antimonate, potassium antimony tartrate or sodium antimony tartrate, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of potassium antimonate and potassium antimony tartrate, a combination of sodium antimonate and potassium antimonate, or a combination of antimony trichloride and sodium antimonate.
[0025] The present invention uses antimony as a doping element, which penetrates into the crystal lattice, replaces part of the transition metal elements, forms a more stable chemical bond with oxygen, stabilizes the crystal structure, inhibits Li-Ni mixing, and improves safety during the electrochemical reaction. At the same time, the interlayer spacing of metal ions can be improved, so that the distance of lithium ion transmission is shortened, and the rate performance of the material is improved.
[0026] Preferably, the mass concentration of the first doping metal source solution in step (1) is 10 g / L to 50 g / L, for example: 1 g / L, 2 g / L, 3 g / L, 4 g / L or 5 g / L, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0027] Preferably, in step (1), the first base liquid contains a first complexing agent and a first precipitating agent.
[0028] Preferably, the pH of the first base solution in step (1) is 10 to 11.5, for example, 10, 10.5, 10.8, 11 or 11.5, etc., but is not limited to the listed values. Other values not listed within the range are also applicable.
[0029] Preferably, the concentration of the first complexing agent in the first base solution in step (1) is 4 g / L to 12 g / L, for example, 4 g / L, 5 g / L, 8 g / L, 10 g / L or 12 g / L, etc., and is not limited to the listed values. Other values not listed within the numerical range are also applicable.
[0030] Preferably, the atmosphere of the first coprecipitation reaction in step (1) comprises nitrogen.
[0031] Preferably, the temperature of the first coprecipitation reaction in step (1) is 40°C to 60°C, for example, 40°C, 45°C, 50°C, 55°C or 60°C, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0032] Preferably, during the first coprecipitation reaction in step (1), the flow rate of the first nickel-cobalt-manganese mixed salt solution is 2 L / h to 4 L / h, for example, 2 L / h, 2.5 L / h, 3 L / h, 3.5 L / h or 4 L / h, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0033] Preferably, during the first coprecipitation reaction in step (1), the mass concentration of the first complexing agent is 4 g / L to 8 g / L, for example, 4 g / L, 5 g / L, 6 g / L, 7 g / L or 8 g / L, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0034] Preferably, the pH of the first coprecipitation reaction in step (1) is 11.2-12.0, for example, 11.2, 11.5, 11.6, 11.8 or 12, etc., not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0035] Preferably, during the first coprecipitation reaction in step (1), the flow rate of the first doping metal source solution is 100 mL / h to 300 mL / h, for example, 100 mL / h, 150 mL / h, 200 mL / h, 250 mL / h or 300 mL / h, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0036] Preferably, the median particle size D50 of the core particles in the core solution of step (1) is 3.5 μm to 5 μm, for example: 3.5 μm, 3.8 μm, 4 μm, 4.5 μm or 5 μm, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] Preferably, the solid content of the second base liquid in step (2) is 100 g / L to 500 g / L, for example: 100 g / L, 200 g / L, 300 g / L, 400 g / L or 500 g / L, etc., not limited to the listed values, other unlisted values within the numerical range are also applicable.
[0038] Preferably, the concentration of the first complexing agent in the second base liquid in step (2) is 2 g / L to 8 g / L, for example, 4 g / L, 4.5 g / L, 5 g / L, 5.5 g / L or 6 g / L, etc., not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0039] Preferably, the pH of the second base solution in step (2) is 10-12, for example, 10, 10.5, 11, 11.5 or 12, etc., but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0040] Preferably, in step (2), the molar ratio of the total molar amount of the doping metal element in the second doping metal source solution to the total molar amount of the nickel, cobalt and manganese elements in the second nickel, cobalt and manganese mixed salt solution is (0.05-5):100, for example: 0.05:100, 0.1:100, 1:100, 2:100 or 5:100, etc., not limited to the listed values, other unlisted values within the numerical range are also applicable, preferably (0.5-1.5):100.
[0041] Preferably, the total mass concentration of nickel ions, cobalt ions and manganese ions in the second nickel-cobalt-manganese mixed salt solution in step (2) is 20 g / L to 120 g / L, for example: 20 g / L, 50 g / L, 80 g / L, 100 g / L or 120 g / L, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0042] Preferably, in step (2), the molar ratio of nickel ions, cobalt ions and manganese ions in the second nickel-cobalt-manganese mixed salt solution is (60-95):(1-20):(1-20), for example: 60:20:20, 65:18:17, 70:15:15, 80:10:10 or 95:2:3, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0043] Preferably, in step (2), the second complexing agent comprises aqueous ammonia.
[0044] Preferably, the mass concentration of the second complexing agent in step (2) is 5% to 10%, for example, 5%, 6%, 8%, 9% or 10%, etc., not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0045] Preferably, in step (2), the second precipitant comprises sodium hydroxide solution.
[0046] Preferably, the mass concentration of the second precipitant in step (2) is 20% to 40%, for example, 20%, 25%, 30%, 35% or 40%, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0047] Preferably, the doping metal source in the second doping metal source solution in step (2) includes any one of a sodium source, a calcium source, a niobium source, a molybdenum source, a tungsten source, a zirconium source or an antimony source, or a combination of at least two of them. Typical but non-limiting combinations include a combination of a sodium source and an antimony source, a combination of an antimony source and a zirconium source, or a combination of an antimony source and a tungsten source, etc., preferably an antimony source.
[0048] Preferably, the antimony source includes any one of antimony trichloride, sodium antimonate, potassium antimonate, potassium antimony tartrate or sodium antimony tartrate, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of potassium antimonate and potassium antimony tartrate, a combination of sodium antimonate and potassium antimonate, or a combination of antimony trichloride and sodium antimonate.
[0049] Preferably, the mass concentration of the second doping metal source solution in step (2) is 10 g / L to 50 g / L, for example: 1 g / L, 2 g / L, 3 g / L, 4 g / L or 5 g / L, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0050] Preferably, the atmosphere of the second coprecipitation reaction in step (2) comprises nitrogen.
[0051] Preferably, the temperature of the second coprecipitation reaction in step (2) is 40°C to 60°C, for example, 40°C, 45°C, 50°C, 55°C or 60°C, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0052] Preferably, during the second co-precipitation reaction in step (2), the flow rate of the second nickel-cobalt-manganese mixed salt solution is 4 L / h to 6 L / h, for example 4 L / h, 4.5 L / h, 5 L / h, 5.5 L / h or 6 L / h, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0053] Preferably, during the second coprecipitation reaction in step (2), the concentration of the second complexing agent is 4 g / L to 8 g / L, for example 4 g / L, 5 g / L, 6 g / L, 7 g / L or 8 g / L, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0054] Preferably, the pH of the second coprecipitation reaction in step (2) is 11 to 13, for example, 11, 11.5, 12, 12.5 or 13, etc., and is not limited to the listed values. Other values not listed within the numerical range are also applicable.
[0055] Preferably, during the second coprecipitation reaction in step (2), the flow rate of the second doping metal source solution is 200 mL / h to 1000 mL / h, for example 200 mL / h, 400 mL / h, 600 mL / h, 800 mL / h or 1000 mL / h, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0056] Preferably, during the second coprecipitation reaction in step (2), the median particle size D50 of the particles in the system increases by 1 μm to 3 μm, for example, 1 μm, 1.5 μm, 2 μm, 2.5 μm or 3 μm, etc., not limited to the listed values, and other values not listed within the numerical range are also applicable. The flow rates of the second nickel-cobalt-manganese mixed salt solution, the second complexing agent, the second precipitating agent and the second doping metal source solution are independently increased by 10% to 30%, for example, 10%, 15%, 20%, 25% or 30%, etc., not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0057] During the second coprecipitation reaction of the present invention, the flow rates of the complexing agent, precipitant, ternary liquid and doped metal salt solution are increased correspondingly for every 1-3 μm growth of the median particle size D50 in the system to maintain a constant growth rate, and the feeding reaction is stopped when the growth particle size reaches the target value.
[0058] Preferably, in step (2), the second coprecipitation reaction is followed by aging, washing and drying.
[0059] Preferably, the bio-based carbon source in step (3) comprises any one of peanut shells, rice husks, mangosteen shells, coconut shells, corn stalks or walnut wood, or a combination of at least two thereof, preferably peanut shells.
[0060] Preferably, the bio-based carbon source is subjected to acidification pretreatment before the carbonization treatment in step (3).
[0061] Preferably, the acidification pretreatment comprises soaking the bio-based carbon source in an acid solution.
[0062] Preferably, the acid solution comprises any one of hydrochloric acid, sulfuric acid or nitric acid, or a combination of at least two of them.
[0063] Preferably, the mass concentration of the acid solution is 10% to 30%, for example, 10%, 15%, 20%, 25% or 30%, etc., and is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0064] Preferably, the immersion temperature is 50°C to 80°C, for example, 50°C, 55°C, 60°C, 70°C or 80°C, etc., and is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0065] Preferably, the soaking time is 60 min to 100 min, for example, 600 min, 700 min, 800 min, 900 min or 1000 min, etc., and is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0066] Preferably, the temperature of the carbonization treatment in step (3) is 400°C to 800°C, for example, 400°C, 500°C, 600°C, 700°C or 800°C, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0067] Preferably, the carbonization treatment time in step (3) is 100 min to 800 min, for example, 100 min, 200 min, 300 min, 500 min or 800 min, etc., not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0068] Preferably, the carbonization treatment in step (3) is followed by a drying treatment.
[0069] Preferably, the temperature of the drying treatment is 80°C to 150°C, for example, 80°C, 90°C, 100°C, 120°C or 150°C, etc., and is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0070] Preferably, the mass ratio of the bio-based carbon-coated material to the doped ternary precursor in step (3) is (1-10):(50-200), for example: 1:50, 2:50, 5:100, 8:20 or 10:200, etc., not limited to the listed values, other unlisted values within the numerical range are also applicable, preferably (1-5):(50-100).
[0071] Preferably, the sintering process in step (3) includes a first sintering process and a second sintering process.
[0072] Preferably, the first sintering temperature is 400°C to 700°C, for example, 400°C, 450°C, 500°C, 600°C or 700°C, etc., and is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0073] Preferably, the first sintering time is 3 h to 6 h, for example, 3 h, 3.5 h, 4 h, 5 h or 6 h, etc., and is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0074] Preferably, the temperature of the second sintering is 700°C to 1000°C, for example, 7000°C, 7500°C, 8000°C, 9000°C or 10000°C, etc., and is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0075] Preferably, the second sintering time is 10 h to 20 h, for example, 10 h, 12 h, 15 h, 18 h or 20 h, etc., and is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0076] In a second aspect, the present invention provides a ternary precursor modified by a bio-based carbon material, wherein the ternary precursor modified by a bio-based carbon material is prepared by the preparation method described in the first aspect.
[0077] In a third aspect, the present invention provides a ternary positive electrode material modified by a bio-based carbon material, wherein the ternary positive electrode material modified by a bio-based carbon material is prepared by mixedly sintering a ternary precursor modified by a bio-based carbon material as described in the second aspect and a lithium source.
[0078] Preferably, the lithium source comprises lithium hydroxide and / or lithium carbonate.
[0079] In a fourth aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises a ternary positive electrode material modified with a bio-based carbon material as described in the third aspect.
[0080] Compared with the prior art, the present invention has the following beneficial effects:
[0081] (1) The present invention adopts a two-step co-precipitation method to adjust the conditions of the co-precipitation reaction to prepare a precursor with high sphericity. During the co-precipitation process, adding a suitable doping element can stabilize the crystal structure and improve the interlayer spacing of the metal ions. Then, the biomass carbon material is coated on the surface of the precursor to improve the cyclic stability of the precursor while achieving the purpose of green environmental protection and reducing costs.
[0082] (2) The lithium-ion battery made from the ternary precursor prepared by the method of the present invention has an initial discharge capacity of more than 203.4 mAh / g, an initial coulombic efficiency of more than 89.6%, and a capacity retention rate of more than 87.2% after 100 cycles. BRIEF DESCRIPTION OF THE DRAWINGS
[0083] Figure 1 This is a surface SEM image of the bio-based carbon material modified ternary precursor obtained in Example 1 of the present invention.
[0084] Figure 2 This is a cross-sectional SEM image of the bio-based carbon material modified ternary precursor obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0085] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0086] Example 1
[0087] This embodiment provides a bio-based carbon material modified ternary precursor, and the bio-based carbon material modified ternary precursor is prepared by the following method:
[0088] (1) A nickel-cobalt-manganese mixed salt solution with a total metal element concentration of 80 g / L and a molar ratio of Ni, Co, and Mn of 94:3:3, a NaOH solution with a mass concentration of 25%, and an ammonia solution with a mass concentration of 7.5%, and a 20 g / L antimony trichloride solution were prepared, wherein the ratio of the molar amount of antimony element in the antimony trichloride solution to the total molar amount of nickel, cobalt, and manganese elements in the nickel-cobalt-manganese mixed salt solution was 1:100. 150 L of pure water and a certain amount of NaOH solution and ammonia solution were added to a 300 L reactor, and 0.8 m 3 / h, nitrogen is introduced into the bottom liquid, stirred at a speed of 200 rpm to mix evenly, then the temperature is raised to 40°C, the pH is controlled to be 11-11.5, and the ammonia concentration is controlled to be 6g / L-8g / L to obtain a bottom liquid, and a nickel-cobalt-manganese mixed salt solution, a NaOH solution, ammonia water and antimony trichloride solution are introduced into the bottom liquid in parallel at 60°C, wherein the flow rate of the nickel-cobalt-manganese mixed salt solution is 4L / h, and the flow rate of the antimony trichloride solution is 200mL / h. During the reaction, the ammonia concentration is 6g / L-8g / L, and the pH is 11.2-11.5. When the internal nucleation is completed and the nucleation grows to 4.5μm, the feeding reaction is stopped to obtain a core solution;
[0089] (2) 100 L of the kernel solution was transferred to another 300 L reactor, 100 L of water was added to control the solid content to 300 g / L, and ammonia water was added to control the ammonia concentration in the reaction system to be in the range of 4 to 6 g / L and the pH to be 11 to 11.2 to obtain a bottom solution, and a nickel-cobalt-manganese mixed salt solution, a NaOH solution, ammonia water and an antimony trichloride solution were introduced into the bottom solution in parallel at 60° C., wherein the flow rate of the nickel-cobalt-manganese mixed salt solution was 6 L / h, the ammonia concentration was 6 g / L to 7 g / L, the pH was 11.5 to 11.8, and the flow rate of the antimony trichloride solution was 500 mL / h. When the particle size grew to 7 μm during the reaction, the flow rate of the nickel-cobalt-manganese mixed salt solution was increased to 8 L / h, and the ammonia solution was added to the bottom solution. The flow rate of water is 1000 ml / L, the flow rate of sodium hydroxide solution is 2.5 L / h, and the flow rate of antimony trichloride solution is 650 mL / h. When the particle size grows to 9.5 μm during the reaction, the flow rate of nickel-cobalt-manganese mixed salt solution is continuously increased to 10 L / h, the flow rate of ammonia water is increased to 1200 ml / L, the flow rate of sodium hydroxide solution is increased to 3 L / h, and the flow rate of antimony trichloride solution is increased to 800 mL / h to maintain a constant growth rate. When the growth particle size reaches 12 μm, the feed reaction is stopped, and the obtained qualified slurry is washed and dried, wherein the washing is performed four times with water, and the drying is performed at a relatively low temperature of 120° C., and finally a doped-modified high-sphericity ternary precursor is formed;
[0090] (3) The peanut shells are crushed and ground, and then sieved through a sieve. The peanut shell powder is soaked and dissolved in a hydrochloric acid solution with a mass concentration of 20%, wherein the soaking temperature is 80°C and the soaking time is 100 minutes. Then it is washed with water twice and placed in a high-temperature furnace for calcination to complete carbonization, wherein the calcination carbonization temperature is 800°C and the time is 600 minutes. The carbonized product is washed with water three times and dried in an oven at 100°C to obtain a bio-based carbon material, and the mass ratio of the doped modified high sphericity ternary precursor to the bio-based carbon material is 100:1. The mixture is sintered in a box furnace, wherein the first stage sintering temperature is 600°C, the time is 4 hours, and the second sintering stage temperature is 950°C, the time is 10 hours, and the ternary precursor modified by the bio-based carbon material is obtained.
[0091] The surface SEM image of the ternary precursor modified by the bio-based carbon material is as follows: Figure 1 As shown by Figure 1 It can be seen that the primary particles of the ternary precursor modified with the bio-based carbon material exhibit a needle-like morphology.
[0092] The cross-sectional SEM image of the ternary precursor modified by the bio-based carbon material is as follows: Figure 2 As shown by Figure 2 It can be seen that the bio-based carbon material modified ternary precursor has a very obvious core structure, and the particle growth presents a radial morphology.+ The transport channel is beneficial to the subsequent electrochemical cycle of Li + De-embedding and de-embedding can improve the rate performance of the material.
[0093] Example 2
[0094] This embodiment provides a bio-based carbon material modified ternary precursor, and the bio-based carbon material modified ternary precursor is prepared by the following method:
[0095] (1) A nickel-cobalt-manganese mixed salt solution with a total metal element concentration of 80 g / L and a molar ratio of Ni, Co, and Mn of 94:3:3, a NaOH solution with a mass concentration of 25%, and an ammonia solution with a mass concentration of 7.5%, and a 20 g / L antimony trichloride solution were prepared, wherein the ratio of the molar amount of antimony element in the antimony trichloride solution to the total molar amount of nickel, cobalt, and manganese elements in the nickel-cobalt-manganese mixed salt solution was 1.5:100. 150 L of pure water and a certain amount of NaOH solution and ammonia solution were added to a 300 L reactor, and 0.8 m 3 / h, nitrogen is introduced into the bottom liquid, and the mixture is stirred at a speed of 200 rpm to be uniformly mixed, and then the temperature is raised to 50°C, the pH is controlled to be 10.5-11, and the ammonia concentration is controlled to be 6g / L-8g / L to obtain a bottom liquid, and a nickel-cobalt-manganese mixed salt solution, a NaOH solution, ammonia water and an antimony trichloride solution are introduced into the bottom liquid in parallel at 55°C, wherein the flow rate of the nickel-cobalt-manganese mixed salt solution is 3L / h, the ammonia concentration is 7g / L-8g / L, and the pH is 11.5-11.8, and the flow rate of the antimony trichloride solution is 150mL / h. When the internal nucleation is completed and the nucleation grows to 5μm, the feeding reaction is stopped to obtain a core solution;
[0096] (2) 100 L of the kernel solution was transferred to another 300 L reactor, 100 L of water was added to control the solid content to 500 g / L, and ammonia water was added to control the ammonia concentration in the reaction system to be in the range of 2-4 g / L and the pH to be 11-11.3, to obtain a bottom solution, and a nickel-cobalt-manganese mixed salt solution, a NaOH solution, ammonia water and antimony trichloride solution were introduced into the bottom solution in parallel at 50° C., wherein the flow rate of the nickel-cobalt-manganese mixed salt solution was 4 L / h, the ammonia concentration was 6 g / L-8 g / L, the pH was 11.2-11.5, and the flow rate of the antimony trichloride solution was 300 mL / h. When the particle size grew to 7.5 μm during the reaction, the flow rate of the nickel-cobalt-manganese mixed salt solution was increased to 5 L / h. The flow rate of ammonia water is 900 ml / L, the flow rate of sodium hydroxide solution is 2.2 L / h, and the flow rate of antimony trichloride solution is 350 mL / h. When the particle size grows to 10 μm during the reaction, the flow rate of nickel-cobalt-manganese mixed salt solution is continued to be increased to 6 L / h, the flow rate of ammonia water is increased to 1080 ml / L, the flow rate of sodium hydroxide solution is increased to 2.5 L / h, and the flow rate of antimony trichloride solution is increased to 420 mL / h to maintain a constant growth rate. When the growth particle size reaches 12.5 μm, the feed reaction is stopped, and the obtained qualified slurry is washed and dried, wherein the washing is performed four times with water, and the drying is performed at a relatively low temperature of 120° C., and finally a doped and modified ternary precursor with high sphericity is formed;
[0097] (3) The peanut shells are crushed and ground, and then sieved through a sieve. The peanut shell powder is soaked and dissolved in a hydrochloric acid solution with a mass concentration of 30%, wherein the soaking temperature is 50°C and the soaking time is 60 minutes. Then it is washed with water twice and placed in a high-temperature furnace for calcination to complete carbonization, wherein the calcination carbonization temperature is 500°C and the time is 800 minutes. The carbonized product is washed with water three times and dried in an oven at 100°C to obtain a bio-based carbon material, and the mass ratio of the doped modified high sphericity ternary precursor to the bio-based carbon material is 100:5. The mixture is sintered in a box furnace, wherein the first stage sintering temperature is 500°C and the time is 5.5 hours, and the second sintering stage temperature is 800°C and the time is 15 hours, to obtain the ternary precursor modified by the bio-based carbon material.
[0098] Example 3
[0099] This embodiment provides a bio-based carbon material modified ternary precursor, and the bio-based carbon material modified ternary precursor is prepared by the following method:
[0100] (1) A nickel-cobalt-manganese mixed salt solution with a total metal element concentration of 80 g / L and a molar ratio of Ni, Co, and Mn of 94:3:3, a NaOH solution with a mass concentration of 25%, and an ammonia solution with a mass concentration of 7.5%, and a 20 g / L antimony trichloride solution were prepared, wherein the ratio of the molar amount of antimony element in the antimony trichloride solution to the total molar amount of nickel, cobalt, and manganese elements in the nickel-cobalt-manganese mixed salt solution was 0.5:100. 150 L of pure water and a certain amount of NaOH solution and ammonia solution were added to a 300 L reactor, and 0.8 m 3 / h, nitrogen is introduced into the bottom liquid, and the mixture is stirred at a speed of 200 rpm to be uniformly mixed, and then the temperature is raised to 50°C, the pH is controlled to be 10.8-11.2, and the ammonia concentration is controlled to be 8g / L-9g / L to obtain a bottom liquid, and a nickel-cobalt-manganese mixed salt solution, a NaOH solution, ammonia water and an antimony trichloride solution are introduced into the bottom liquid in parallel at 50°C, wherein the flow rate of the nickel-cobalt-manganese mixed salt solution is 3L / h, the ammonia concentration is 7g / L-8g / L, and the pH is 11.2-11.5, and the flow rate of the antimony trichloride solution is 150mL / h, and the feeding reaction is stopped when the internal nucleation is completed and the nucleation grows to 5μm, to obtain a core solution;
[0101] (2) 100 L of the core solution was transferred to another 300 L reactor, 100 L of water was added to control the solid content to 100 g / L, and ammonia water was added to control the ammonia concentration in the reaction system to be in the range of 6 to 8 g / L and the pH to be 11 to 11.3 to obtain a bottom solution, and a nickel-cobalt-manganese mixed salt solution, a NaOH solution, ammonia water and antimony trichloride solution were introduced into the bottom solution in parallel at 50° C., wherein the flow rate of the nickel-cobalt-manganese mixed salt solution was 6 L / h, the ammonia concentration was 6 g / L to 7 g / L, the pH was 11.5 to 11.8, and the flow rate of the antimony trichloride solution was 400 mL / h. When the particle size grew to 7 μm during the reaction, the flow rate of the nickel-cobalt-manganese mixed salt solution was increased to 6.6 L / h. The flow rate of ammonia water is 1100 ml / L, the flow rate of sodium hydroxide solution is 2.2 L / h, and the flow rate of antimony trichloride solution is 450 mL / h. When the particle size grows to 9 μm during the reaction, the flow rate of nickel-cobalt-manganese mixed salt solution is continued to be increased to 7.3 L / h, the flow rate of ammonia water is increased to 1320 ml / L, the flow rate of sodium hydroxide solution is increased to 2.5 L / h, and the flow rate of antimony trichloride solution is increased to 500 mL / h to maintain a constant growth rate. When the growth particle size reaches 12 μm, the feed reaction is stopped, and the obtained qualified slurry is washed and dried, wherein the washing is performed four times with water, and the drying is performed at a relatively low temperature of 120° C., and finally a doped-modified high-sphericity ternary precursor is formed;
[0102] (3) The peanut shells are crushed and ground, and then sieved through a sieve. The peanut shell powder is soaked and dissolved in a hydrochloric acid solution with a mass concentration of 20%, wherein the soaking temperature is 50°C and the soaking time is 80 minutes. Then it is washed with water twice and placed in a high-temperature furnace for calcination to complete carbonization, wherein the calcination carbonization temperature is 600°C and the time is 600 minutes. The carbonized product is washed with water three times and dried in an oven at 100°C to obtain a bio-based carbon material, and the mass ratio of the doped modified high sphericity ternary precursor to the bio-based carbon material is 50:1. The mixture is sintered in a box furnace, wherein the first stage sintering temperature is 400°C and the time is 6 hours, and the second sintering stage temperature is 700°C and the time is 20 hours, to obtain the ternary precursor modified by the bio-based carbon material.
[0103] Example 4
[0104] The only difference between this embodiment and embodiment 1 is that the ratio of the molar amount of antimony element in the antimony trichloride solution to the total molar amount of nickel, cobalt and manganese elements in the nickel, cobalt and manganese mixed salt solution is 0.1:100, and other conditions and parameters are exactly the same as those in embodiment 1.
[0105] Example 5
[0106] The only difference between this embodiment and embodiment 1 is that the ratio of the molar amount of antimony element in the antimony trichloride solution to the total molar amount of nickel, cobalt and manganese elements in the nickel, cobalt and manganese mixed salt solution is 2:100, and other conditions and parameters are exactly the same as those in embodiment 1.
[0107] Example 6
[0108] The only difference between this embodiment and embodiment 1 is that peanut shells are replaced with rice husks, and other conditions and parameters are exactly the same as those in embodiment 1.
[0109] Example 7
[0110] The only difference between this embodiment and embodiment 1 is that peanut shells are replaced with corn stalks, and other conditions and parameters are exactly the same as those in embodiment 1.
[0111] Example 8
[0112] The only difference between this embodiment and embodiment 1 is that the mass ratio of the doped and modified high-sphericity ternary precursor to the bio-based carbon material is 8:50, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0113] Example 9
[0114] The only difference between this embodiment and embodiment 1 is that the mass ratio of the doped and modified high-sphericity ternary precursor to the bio-based carbon material is 150:1, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0115] Example 10
[0116] The difference between this embodiment and embodiment 1 is that the flow rate of the nickel-cobalt-manganese mixed salt solution in step (2) is 6 L / h, the flow rate of the ammonia water is 1000 ml / L, the flow rate of the sodium hydroxide solution is 2 L / h, and the flow rate of the antimony trichloride solution is 400 mL / h, which remain unchanged until the particle size reaches 12 μm. The other conditions and parameters are exactly the same as those in embodiment 1.
[0117] Comparative Example 1
[0118] The only difference between this comparative example and Example 1 is that no antimony chloride solution is added, and other conditions and parameters are exactly the same as those in Example 1.
[0119] Comparative Example 2
[0120] The only difference between this comparative example and Example 1 is that the doped ternary precursor is directly prepared by a one-step co-precipitation method, and the other conditions and parameters are exactly the same as those in Example 1.
[0121] Example 3
[0122] The only difference between this comparative example and Example 1 is that step (3) is not performed, and the other conditions and parameters are exactly the same as those in Example 1.
[0123] Comparative Example 4
[0124] In this comparative example, peanut shells are replaced with carbon nanotubes, and the preparation method is as follows: multi-walled carbon nanotubes are activated to obtain a suspension containing carbon nanotubes with a concentration of 5 g / L, and the doped and modified high-sphericity ternary precursor prepared in step (2) of Example 1 is added, stirred and ultrasonicated at 1.0 kW for 30 minutes, then filtered and washed with clean water five times, and then dried in an oven at 100°C to obtain a carbon nanotube-coated doped precursor.
[0125] Performance Test:
[0126] The ternary precursors prepared in the embodiments and comparative examples were mixed with lithium hydroxide in the ratio of Li:(Ni+Co+Mn)=1:1, sintered at 500°C for 5h and sintered at 750°C for 20h to obtain a ternary positive electrode material. The ternary positive electrode material was used as the positive electrode active material and mixed with conductive carbon and PVDF in a ratio of 94:3:3. The mixture was then dispersed in methyl pyrrolidone (NMP) as a solvent to obtain a positive electrode slurry, which was evenly coated on an aluminum foil. After coating, the current collector was punched to obtain a coin-shaped electrode, which was vacuum dried at 120°C overnight to obtain a positive electrode sheet. Metallic lithium was selected as the negative electrode, and 1M LiPF6 was dissolved in EC and DMC solvents (volume ratio of 3:7) as the electrolyte. The positive electrode, the negative electrode, and the separator were wound to prepare a battery cell, which was then assembled into a lithium-ion battery through packaging, liquid injection, formation, and volume separation.
[0127] The prepared lithium-ion battery was subjected to electrochemical performance testing. At 0.1C, the + ) between 200 and 250 cycles. The first discharge capacity and first efficiency were measured, and the discharge capacity at the 100th time was used to obtain the capacity retention rate after 100 cycles. The test results are shown in Table 1:
[0128] Table 1
[0129] First discharge capacity (mAh / g) First coulombic efficiency (%) Capacity retention rate (%) Example 1 218.2 95.4 91.5 Example 2 211.2 92.4 89.8 Example 3 209.7 91.8 89.6 Example 4 206.9 90.9 89.1 Example 5 203.4 89.6 87.2 Example 6 210.2 93.5 90.7 Example 7 208.4 92.9 90.4 Example 8 212.5 93.1 90.3 Example 9 210.7 93.4 91.0 Example 10 204.5 90.1 87.7 Comparative Example 1 198.3 87.5 86.1 Comparative Example 2 196.8 86.8 85.9 Comparative Example 3 201.6 88.7 86.8 Comparative Example 4 207.7 91.2 89.5
[0130] As can be seen from Table 1, from Examples 1-10, the first discharge capacity of the lithium-ion battery made from the ternary precursor prepared by the method of the present invention can reach more than 203.4 mAh / g, the first coulombic efficiency can reach more than 89.6%, and the capacity retention rate after 100 cycles can reach more than 87.2%.
[0131] By comparing Example 1 with Examples 4-5, it can be seen that in the preparation process of the ternary precursor modified by the bio-based carbon material of the present invention, the molar ratio between the doping metal in the doping metal source solution and the nickel, cobalt and manganese in the nickel, cobalt and manganese mixed salt solution will affect its performance. The molar ratio of the doping metal to the nickel, cobalt and manganese is controlled at (0.5-1.5):100, and the performance of the ternary precursor modified by the bio-based carbon material is better. If the amount of doping metal added is too large, more transition metal ion sites will be occupied, and the discharge capacity of the material will be limited. At the same time, the lattice distortion effect will also deteriorate the electrochemical performance. If the amount of doping metal added is too small, the transition metal ion interlayer spacing is limited and the doping effect cannot be achieved.
[0132] By comparing Example 1 with Examples 6-7, it can be seen that in the preparation process of the bio-based carbon material modified ternary precursor of the present invention, the weight of the biomass carbon material will affect its performance, and the use of peanut shells as the biomass carbon material can greatly improve the performance of the ternary precursor.
[0133] By comparing Example 1 with Examples 8-9, it can be seen that in the preparation process of the bio-based carbon material modified ternary precursor of the present invention, the mass ratio of the doped modified high-sphericity ternary precursor to the bio-based carbon material will affect its performance. By controlling the mass ratio of the doped modified high-sphericity ternary precursor to the bio-based carbon material to be (1-5): (50-100), the performance of the bio-based carbon material modified ternary precursor is better. If the amount of bio-based carbon material added is too large, the carbon protective layer formed on the surface of the material will also be too thick, which is not conducive to the transmission of lithium ions. At the same time, if the amount of bio-based carbon material added is too small, the protective effect of the carbon protective layer is limited, and the electrolyte is easy to penetrate into the interior of the material during the cycle, and the cycle performance is deteriorated.
[0134] By comparing Example 1 and Example 10, it can be seen that during the second co-precipitation reaction of the present invention, the flow rates of the complexing agent, precipitant, ternary liquid and doped metal salt solution are increased correspondingly for every 1 to 3 μm growth of the median particle size D50 in the system to maintain a constant growth rate, thereby significantly improving the performance of the ternary precursor.
[0135] From the comparison between Example 1 and Comparative Example 1, it can be seen that the present invention uses antimony as a doping element, and the antimony element penetrates into the crystal lattice, replaces part of the transition metal element, forms a more stable chemical bond with oxygen, stabilizes the crystal structure, inhibits Li-Ni mixing, and improves the safety during the electrochemical reaction. At the same time, the interlayer spacing of metal ions can be improved, so that the distance of lithium ion transmission is shortened, and the rate performance of the material is improved.
[0136] From the comparison between Example 1 and Comparative Example 2, it can be seen that the present invention prepares the ternary precursor by a two-step co-precipitation method, which can significantly improve the uniformity and consistency of the precursor growth and improve the sphericity of the precursor.
[0137] By comparing Example 1 with Comparative Examples 3-4, it can be seen that the ternary precursor of the present invention uses environmentally friendly biomass carbon materials as coating agents to obtain ternary positive electrode materials that are no worse than carbon nanotubes and other carbon materials coating, which is not only green and environmentally friendly but also greatly reduces costs.
[0138] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a ternary precursor modified by a bio-based carbon material, characterized in that: The preparation method comprises the following steps: (1) injecting a first nickel-cobalt-manganese mixed salt solution, a first complexing agent, a first precipitant, and a first doping metal source solution into a first base solution in parallel to perform a first coprecipitation reaction to obtain a core solution; (2) adjusting the solid content of the core solution and the concentration of the first complexing agent to obtain a second base solution, and injecting a second nickel-cobalt-manganese mixed salt solution, a second complexing agent, a second precipitant, and a second doping metal source solution into the second base solution in parallel to perform a second coprecipitation reaction to obtain a doped ternary precursor; (3) Carbonizing the bio-based carbon source to obtain a bio-based carbon-coated material, mixing the bio-based carbon-coated material with a doped ternary precursor, and sintering the mixture to obtain the ternary precursor modified by the bio-based carbon material.
2. The preparation method according to claim 1, characterized in that Step (1) The molar ratio of the total molar amount of the doping metal element in the first doping metal source solution to the total molar amount of the nickel, cobalt and manganese elements in the first nickel, cobalt and manganese mixed salt solution is (0.05-5):100, preferably (0.5-1.5):100; Preferably, in step (1), the total mass concentration of nickel ions, cobalt ions and manganese ions in the first nickel-cobalt-manganese mixed salt solution is 20 g / L to 120 g / L; Preferably, in step (1), the molar ratio of nickel ions, cobalt ions and manganese ions in the first nickel-cobalt-manganese mixed salt solution is (60-95):(1-20):(1-20); Preferably, in step (1), the first complexing agent comprises aqueous ammonia; Preferably, the mass concentration of the first complexing agent in step (1) is 5% to 10%; Preferably, in step (1), the first precipitant comprises a sodium hydroxide solution; Preferably, the mass concentration of the first precipitant in step (1) is 20 g / L to 40 g / L; Preferably, the doping metal source in the first doping metal source solution in step (1) comprises any one of an aluminum source, a titanium source, a niobium source, a zirconium source, a tungsten source, a vanadium source, a strontium source, a gallium source, a cerium source, a yttrium source, a lanthanum source or an antimony source, or a combination of at least two thereof, preferably an antimony source; Preferably, the antimony source includes any one or a combination of at least two of antimony trichloride, sodium antimonate, potassium antimonate, potassium antimony tartrate or sodium antimony tartrate; Preferably, the mass concentration of the first doping metal source solution in step (1) is 10 g / L to 50 g / L; Preferably, in step (1), the first base solution contains a first complexing agent and a first precipitating agent; Preferably, the pH of the first base solution in step (1) is 10 to 11.5; Preferably, the concentration of the first complexing agent in the first base solution in step (1) is 4 g / L to 12 g / L.
3. The preparation method according to claim 1 or 2, characterized in that: Step (1) The atmosphere of the first coprecipitation reaction includes nitrogen; Preferably, the temperature of the first coprecipitation reaction in step (1) is 40°C to 60°C; Preferably, during the first coprecipitation reaction in step (1), the flow rate of the first nickel-cobalt-manganese mixed salt solution is 2 L / h to 4 L / h; Preferably, during the first coprecipitation reaction in step (1), the mass concentration of the first complexing agent is 4 g / L to 8 g / L; Preferably, the pH of the first coprecipitation reaction in step (1) is 11.2 to 12.0; Preferably, during the first coprecipitation reaction in step (1), the flow rate of the first doping metal source solution is 100 mL / h to 300 mL / h; Preferably, the median particle size D50 of the core particles in the core solution in step (1) is 3.5 μm to 5 μm.
4. The preparation method according to any one of claims 1 to 3, characterized in that: Step (2) The solid content of the second base liquid is 100 g / L to 500 g / L; Preferably, in step (2), the concentration of the first complexing agent in the second base solution is 2 g / L to 8 g / L; Preferably, the pH of the second base solution in step (2) is 10 to 12; Preferably, in step (2), the molar ratio of the total molar amount of the doping metal element in the second doping metal source solution to the total molar amount of the nickel, cobalt and manganese elements in the second nickel, cobalt and manganese mixed salt solution is (0.05-5):100, preferably (0.5-1.5):100; Preferably, in step (2), the total mass concentration of nickel ions, cobalt ions and manganese ions in the second nickel-cobalt-manganese mixed salt solution is 20 g / L to 120 g / L; Preferably, in step (2), the molar ratio of nickel ions, cobalt ions and manganese ions in the second nickel-cobalt-manganese mixed salt solution is (60-95):(1-20):(1-20); Preferably, the second complexing agent in step (2) comprises aqueous ammonia; Preferably, the mass concentration of the second complexing agent in step (2) is 5% to 10%; Preferably, the second precipitant in step (2) comprises a sodium hydroxide solution; Preferably, the mass concentration of the second precipitant in step (2) is 20% to 40%; Preferably, the doping metal source in the second doping metal source solution in step (2) comprises any one of a sodium source, a calcium source, a niobium source, a molybdenum source, a tungsten source, a zirconium source or an antimony source, or a combination of at least two thereof, preferably an antimony source; Preferably, the antimony source includes any one or a combination of at least two of antimony trichloride, sodium antimonate, potassium antimonate, potassium antimony tartrate or sodium antimony tartrate; Preferably, in step (2), the mass concentration of the second doping metal source solution is 10 g / L to 50 g / L.
5. The preparation method according to any one of claims 1 to 4, characterized in that: Step (2) The atmosphere of the second coprecipitation reaction includes nitrogen; Preferably, the temperature of the second coprecipitation reaction in step (2) is 40°C to 60°C; Preferably, during the second coprecipitation reaction in step (2), the flow rate of the second nickel-cobalt-manganese mixed salt solution is 4 L / h to 6 L / h; Preferably, during the second coprecipitation reaction in step (2), the concentration of the second complexing agent is 4 g / L to 8 g / L; Preferably, the pH of the second coprecipitation reaction in step (2) is 11 to 13; Preferably, during the second coprecipitation reaction in step (2), the flow rate of the second doping metal source solution is 200 mL / h to 1000 mL / h; Preferably, during the second coprecipitation reaction in step (2), the flow rates of the second nickel-cobalt-manganese mixed salt solution, the second complexing agent, the second precipitant and the second doping metal source solution are independently increased by 10% to 30% for every 1 μm to 3 μm increase in the median particle size D50 of the particles in the system; Preferably, in step (2), the second coprecipitation reaction is followed by aging, washing and drying.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The bio-based carbon source in step (3) comprises any one of peanut shells, rice husks, mangosteen shells, coconut shells, corn stalks or walnut wood, or a combination of at least two of them, preferably peanut shells; Preferably, the bio-based carbon source is subjected to acidification pretreatment before the carbonization treatment in step (3); Preferably, the acidification pretreatment comprises soaking the bio-based carbon source in an acid solution; Preferably, the acid solution comprises any one of hydrochloric acid, sulfuric acid or nitric acid, or a combination of at least two thereof; Preferably, the mass concentration of the acid solution is 10% to 30%; Preferably, the soaking temperature is 50°C to 80°C; Preferably, the soaking time is 60 min to 100 min; Preferably, the temperature of the carbonization treatment in step (3) is 400° C. to 800° C.; Preferably, the carbonization treatment time in step (3) is 100 min to 800 min; Preferably, the carbonization treatment in step (3) is followed by a drying treatment; Preferably, the temperature of the drying treatment is 80°C to 150°C.
7. The preparation method according to any one of claims 1 to 6, characterized in that: In step (3), the mass ratio of the bio-based carbon coating material to the doped ternary precursor is (1-10):(50-200), preferably (1-5):(50-100); Preferably, the sintering process in step (3) includes a first sintering and a second sintering; Preferably, the first sintering temperature is 400°C to 700°C; Preferably, the first sintering time is 3h to 6h; Preferably, the second sintering temperature is 700°C to 1000°C; Preferably, the second sintering time is 10 h to 20 h.
8. A ternary precursor modified by a bio-based carbon material, characterized in that: The bio-based carbon material modified ternary precursor is prepared by the preparation method as described in any one of claims 1-7.
9. A ternary positive electrode material modified by a bio-based carbon material, characterized in that: The bio-based carbon material-modified ternary positive electrode material is prepared by mixing and sintering the bio-based carbon material-modified ternary precursor as claimed in claim 8 with a lithium source.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the ternary positive electrode material modified with the bio-based carbon material as claimed in claim 9.
Citation Information
Patent Citations
Carbon-coated ternary anode material and preparing method thereof, and lithium ion battery
CN104882589A
Wet doping and carbon coating co-modified quaternary positive electrode material and preparation method thereof
CN113443659A
Nickel-manganese binary composite positive electrode material and preparation method thereof
CN114057236A
Double-metal alternately-doped nickel-manganese precursor as well as preparation method and application thereof
CN114988491A
Nickel-rich aluminum-doped nickel-cobalt-manganese ternary precursor and preparation method thereof
CN117509756A
Cited By
Boron gradient doped positive electrode precursor, preparation method thereof, positive electrode material and battery
CN120622564A
Core-shell type rare earth gradient doped positive electrode material and preparation method and application thereof
CN121260764A
A core-shell type rare earth gradient doped positive electrode material and a preparation method and application thereof
CN121260764B